Growing and Building: Collaboration of Urban Poverty Reduction Strategy - Rahajuni, Dijan; Badriah, Lilis Siti; Lestari, Sri; Rafinda, Ascaryan (Journal of Social Economics Research, 2019)
This research aims to examine the collaboration strategy for poverty alleviation in Indonesia. The shifting of government program from PNPM-MP to No-Slum City (Kotaku) to alleviate poverty need another strategy to harmonize in-time between both programs. Previous experience found that PNPM-MP has been able to reduce urban poverty, even though it has not yet reached the realization of community welfare. Therefore PNPM-MP is feasible to continue, especially considering that there are still revolving funds managed by the community self-help group (KSM) to meet economic needs and increase productive economic activities. The end of PNPM-PM to the No-Slum City program (Kotaku) requires a reorientation of the strategy to continue reducing poverty and improving people’s welfare. This research using qualitative data to examine the program. Documentation, interview, and survey conducted to collect all the data. Finally, this research using SWOT analysis, an alternative strategy for collaborating the two programs is the grow and build strategy. This research found that using internal and external matrix strategy, in this harmonization program, grow and build strategy needed to minimize the clash between two programs. Further, we need to identify the details strategy that needed to be applied in this shifting program.